New Treatment Perspectives in Adolescents With Anorexia Nervosa: The Efficacy of Non-invasive Brain-Directed Treatment - Costanzo, Floriana; Menghini, Deny; Maritato, Antonella; Castiglioni, Maria C.; Mereu, Alberta; Varuzza, Cristiana; Zanna, Valeria; Vicari, Stefano (Frontiers in Behavioral Neuroscience, 2018)
Poor treatment outcomes are available for Anorexia Nervosa (AN) and treatment innovations are urgently needed. Recently, non-invasive neuromodulation tools have suggested to have potential for reducing AN symptomatology targeting brain alterations. The objective of the study was to verify whether left anodal/right cathodal prefrontal cortex transcranial direct current stimulation (tDCS), may aid in altering/resetting inter-hemispheric balance in patients with AN, re-establishing control over eating behaviors. Twenty-three adolescents with AN underwent a treatment as usual (AU), including nutritional, pharmacological and psychoeducational treatment, plus 18 sessions of tDCS (TDCS+AU = n11; mean age 13.87, SD = 1.8 years) or a Family Based Therapy (FBT+AU = n12, age 15.07, SD = 1.5 years. Psychopathological scales and the body mass index (BMI) were assessed before and after treatment. After six weeks of treatment, the BMI values increased only in the tDCS group, even at one-month follow-up. Independently of the treatment, all participants improved in several psychopathological measures, included AN psychopathology and mood and anxiety symptoms. Our results demonstrated for the first time a specific effect of the left anodal/right cathodal tDCS treatment protocol on stable weight gain and a superiority compared to an active control treatment for adolescents with AN. Results were interpreted as a possible direct/indirect effect of tDCS in into some pathophysiological mechanisms of AN, involving the mesocortical dopaminergic pathways and the promotion of food intake. This pilot study opens new perspectives in the treatment of AN in adolescence, supporting the targeted and beneficial effects of a brain-based treatment.